Risk Mitigation Effects for Mudhārabah Financing Accounting Treatment (Case Study at Bank - Muslina, Muslina; Syahputra, Angga (AL-QARDH, 2021)
Mudharabah financing has a high level of risk caused by moral hazard and adverse selection. The existence of these two risks resulted in a simultaneous impact on the reputation and liquidity of the bank